Why Did my Patient get this Kidney Problem after Receiving this New Cancer Drug?. Issue 1 (January 2017) - Sathick, Insara Jaffer; Seshan, Surya V.; Glezerman, Ilya G.
Novel anticancer therapies are changing the landscape of clinical oncology and nephrology practice. With improved survival rates, many cancer survivors are developing kidney disease as a result of their cancer treatment. As a consequence, a new medical sub-specialty has emerged, termed "onco-nephrology." Onco-nephrology is a broad term encompassing acute and chronic kidney disease from cancer therapy as well as other effects, such as hypertension and electrolyte disturbances. For the practicing nephrologist, it is important to be aware of emerging toxicities from relatively newer anticancer therapies. In this review, we provide an update on the renal toxicity of emerging anticancer therapies, including immune checkpoint inhibitors, angiogenesis inhibitors, and BRAF inhibitors.